Working with multinational and multicultural crews : a Croatian seafarers' perspective - Galešić, Antonio-Džordž (Array, 2019)
Nowadays most of the vessels in the global merchant fleet are manned by multinational and multicultural crews. Working together with mixed crews on board ships can lead to potential misunderstandings and miscommunication, thus causing a potential threat to safety. Since Croatian seafarers frequently sail in mixed crews, a brief research was conducted using the method of questionnaire to elicit their views and opinions regarding the work within multinational and multicultural crews on board merchant vessels, the impact such crews have on the operation of the vessel and challenges they may pose. The questionnaire also elicited Croatian seafarers’ views on the importance of cross-cultural training.